2010
DOI: 10.1039/b920992a
|View full text |Cite
|
Sign up to set email alerts
|

Anion variation on a cobalt(iii) complex of salen-type ligand tethered by four quaternary ammonium salts for CO2/epoxide copolymerization

Abstract: Anion exchange of BF(4)(-) occurs by stirring a cobalt(III) complex of salen-type ligand tethered by four quaternary ammonium BF(4)(-) salts over a slurry of NaX in CH(2)Cl(2), affording a complex containing four X's per cobalt (X = 2,4,5-trichlorophenolate, 6; X = 4-nitrophenolate, 10; X = 2,4-dichlorophenolate, 12). The (1)H and (13)C NMR spectra are in agreement with an unusual imine uncoordinated structure. The two salen-phenoxys and the two X's persistently coordinate with cobalt(III) to form a square pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(39 citation statements)
references
References 52 publications
0
39
0
Order By: Relevance
“…17 Later improvements involved exchanging the 2,4-dinitrophenoxides for 2,4-dichlorophenoxides or 4-nitrophenoxides for increased laboratory safety. 19 Similarly great activity has been found utilizing the asymmetric (salen)CoX complexes 3 and 4 synthesized by Lu et al, featuring an appended bulky amine or quaternary ammonium salt at the 3-position of one phenyl ring, respectively (Fig. 4).…”
Section: Catalytic Improvementsmentioning
confidence: 95%
“…17 Later improvements involved exchanging the 2,4-dinitrophenoxides for 2,4-dichlorophenoxides or 4-nitrophenoxides for increased laboratory safety. 19 Similarly great activity has been found utilizing the asymmetric (salen)CoX complexes 3 and 4 synthesized by Lu et al, featuring an appended bulky amine or quaternary ammonium salt at the 3-position of one phenyl ring, respectively (Fig. 4).…”
Section: Catalytic Improvementsmentioning
confidence: 95%
“…Preparation of 1 and polymerization were carried out through the reported method and conditions [6,13].…”
Section: General Remarksmentioning
confidence: 99%
“…Binding situates both components in proximity regardless of low catalyst concentration or high polymerization temperature, consequently resulting in high turnover number (TON) and turnover frequency (TOF). Later, we found that complex 1 adopts an unusual binding mode, where the imine-nitrogens on the Salen-type ligand do not coordinate but, instead, the counter anions of the tethered quaternary ammonium units coordinate with cobalt [12,13]. Complex 1 displays a high TON of up to 16,000 and TOF of 16000 h À1 .…”
Section: Introductionmentioning
confidence: 96%
“…6 Also, CO 2 can be considered a renewable resource, 7 so its utilization is preferred over dwindling fossil fuels that are still the main basis for commercial polycarbonate synthesis. For example, complexes with Zn, [10][11][12] Al, 13 Co, [14][15][16][17][18][19][20][21] Fe, [22][23] Mg, 24 and Cr [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] have proven to be active in CO 2 /epoxide copolymerization. 9 Recently, a large number of complexes have been developed as active catalyst precursors for the copolymerization of CO 2 and epoxides.…”
Section: Introductionmentioning
confidence: 99%